Produksi Protein Sel Tunggal dari Kultur Bacillus cereus dengan Medium Limbah Cair Tahu - Basaniah Basaniah; Yayuk Putri Rahayu; Haris Munandar Nasution; Gabena Indrayani Dalimunthe (Lembaga Pengembangan Kinerja Dosen, 2024)
Single Cell Protein (PST) is the term used for proteins derived from microbes such as fungi, yeasts and bacteria. One way to deal with the abundance of tofu liquid waste is by using microbiological methods, namely utilizing tofu liquid waste as a substrate for the growth of Bacillus cereus microbial growth for single cell protein production. The purpose of this study was to determine whether tofu liquid waste could produce single cell protein from B. cereus culture and to determine the difference in protein production by adding nutrients to the fermentation medium. The research method used was experimental research, with the independent variables being MFLT1 fermentation medium (Tofu Liquid Waste Fermentation Medium with the addition of KH2PO4 nutrients and sugar) and MFLT2 medium (Tofu Liquid Waste Fermentation Medium with the addition of nutrients KH2PO4; (NH4)2SO4 and sugar); and the length of fermentation on days 0, 2, 4 and 6. While the dependent variables were the analysis of protein content, cell dry weight, glucose content, pH and temperature. The result data in this study were statistically analyzed using the two way Anova method. The results of this study showed that the highest protein content was obtained in MFLT2 medium, namely 0.73% (day 4); cell dry weight 0.253 g; glucose level 1.3339%; pH 3.9 and temperature 29.2oC. Meanwhile, in MFLT1 medium, the highest protein content was 0.46% (4th day); cell dry weight 0.286 g; glucose level 1.3342%; pH 3.9 and temperature 28.8oC. From the research that has been carried out, it can be concluded that tofu liquid waste can produce single cell protein from B. cereus culture and there are differences in protein production results with the addition of nutrients, where the protein content in MFLT2 medium is higher than protein content in MFLT1 medium.